Handloom Weaving in Assam: Problems and Prospects (Global Journal of Human-Social Science, 2012)
The Handloom sector plays a very important role in India s economy It is a part of our culture and heritage and one of the largest economic activities after agriculture having the capacity of absorbing a greater number of manpower In 2009-101 this sector provides direct employment to over 65 lakhs persons in India of which 60 40 are women This sector contributes nearly 19 of the total cloth produced in the country and also adds substantially to export earnings The ratio of handloom to power loom in terms of cloth in 2009-10 was 1 5 55